Points South: Ambrose Bierce, Jorge Luis Borges, and the Fantastic - Howard M. Fraser (Studies in 20th & 21st Century Literature, 1977)
The debt of Borges's "A Secret Miracle" to Ambrose Bierce's "An Occurrence at Owl Creek Bridge" both in theme and technique has been noted in recent criticism. However, a careful study of the two works reveals striking differences, particularly with respect to the treatment of time. Based on Todorov's study of the fantastic, this article attempts to show how Bierce's influence on Borges parallels the general development of psychological realism and its transformation into surrealism. While it is true that the allusive qualities of Borges' work recall thematic and technical aspects of Bierce, nonetheless the American Hispanophile is a precursor of the Argentine Anglophile in only a limited sense.
Keywords: Ambrose Bierce; Jorge Luis Borges; A Secret Miracle; An Occurrence at Owl Creek Bridge; time; psychological realism; surrealism; the fantastic